CORPORATE SOCIAL RESPONSIBILITY SEBAGAI PEMEDIASI PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS DAN LEVERAGE PADA NILAI PERUSAHAAN - Kusumayanti, Ni Ketut Ratna; Astika, Ida Bagus Putra (E-Jurnal Akuntansi; Vol 15 No 1 (2016), 2016)
The purpose of this study was to obtain empirical evidence of CSR's role in mediating the relationship between firm size, profitability and leverage on the firm value. This research was conducted on banking companies listed in the Indonesia Stock Exchange (BEI) 2010-2014. The sampling method using nonprobability sampling with purposive sampling technique. The number of samples obtained are 30 companies with a total of 150 observations. The analysis technique used path analysis. Based on the results of the study found that the variables that has a direct influence on firm value are firm size with positive influence and CSR with negative influence. Meanwhile, the variable that has a direct influence on CSR is firm size with positive influence. Based on the results of the analysis also found that CSR is not able to mediate the relationship between firm size, profitability, and leverage on the firm value.
Keywords: Size, Profitability, Leverage, CSR, Value